Traduire la xéno-encyclopédie en finnois et en français : une approche pragmatique - Martin Carayol (ReS Futurae, 2024)
The translation of neologisms is of particular importance in works of science fiction, where they are often abundant because of their role in the development of the « xeno-encylopedia », the body of knowledge relating to the fictional world constructed by the work. Confronted with the lexical inventiveness of the author, the translator may find himself in difficulty when faced with the need to find an equivalent as close as possible to the original. This article examines Finnish and French translations of the numerous xeno-encyclopedic terms (neologisms, neosemes and proper nouns) found in five short stories by Jack Vance and two cycles by Michael Moorcock, in order to categorise these translations on a pragmatic basis, according to the differential between the effect on the reader in the original language and the effect on the reader in translation. The xeno-encyclopedic terms translated may have the same meaning and connotations as in the original, or they may differ in meaning, register, connotation and so on. In some cases, the translator refrains from translating neologisms, and in others, on the contrary, the translator may introduce neologisms.